Progressive Politeness in the Discourse of the Debate of Indonesian Presidential and Vice Presidential Candidates in 2024 as Teaching Material for Indonesian Speech Texts - Arifin, David Yenu; Prayitno, Harun Joko (Universitas Pahlawan Tuanku Tambusai, 2025)
Politeness is a part of politeness in using language when communicating verbally and in writing. In this study, the principle of politeness is used to confront each other when debating must use strategies and language that fall within the scope of the maxims of the right principles of manners. The research aims to describe progressive politeness in the debate of presidential and vice presidential candidates in 2024, this is done to be a reference in learning Indonesian speech texts about the importance of language politeness in the debate reflecting the level of language that is in accordance with the ability of students, so that the material can be used as a concrete reference that is easy to understand and contextual for students. The research uses a descriptive qualitative approach method, a descriptive qualitative method to describe social reality in a complex way by describing, analyzing, and interpreting data according to the conditions in the object to be studied. Research data was obtained through documentation techniques used to download debate videos and transcribe data, After that the listening technique was continued, this listening technique does not involve the researcher in the conversation, but the researcher is only as a tapping on the conversation between the speaker and the opponent. The recording technique is carried out at the same time as the listening technique, the recorded speech is in the form of oral speech from a youtube video so that it turns into a form of written notes. The data that has been collected is then transcribed and analyzed using the theory of politeness according to Leech (2015) which is described into six parts, namely, the maxim of wisdom, the maxim of generosity, the maxim of appreciation, the maxim of moderation, the maxim of consensus, and the maxim of sympathy. This study uses the YouTube channels Chanel Tv Sukabumi, BeritaSatu, Kompas Tv, Kompas Tv Sukabumi as an object to carry out research that refers to the validity of the research. The results of this study are expected to describe the speeches delivered in the debate, students not only learn about the structure and use of language, but also understand the importance of choosing the right words, intonation, and speech attitudes according to who their speaking partners are and in accordance with the context of the ongoing communication situation.